Strategi Pembelajaran Ekspositori pada Pelajaran PAI di SMP Vijaya Kusuma Kota Bandung - Muhamad Ihsan Taufik; Siti Latipah; Aisyah Nawawiyah; Sri Jumriani Puarada; Dadang Hidayat (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2023)
This study aims to identify and analyze the expository learning strategies used in teaching PAI lessons at Vijaya Kusuma Junior High School in Bandung City. This study used descriptive qualitative research method. Data were obtained through classroom observations and interviews with PAI teachers at Vijaya Kusuma Junior High School. The teachers who participated in this study were selected based on purposive sampling method. The results of this study show that PAI teachers in Vijaya Kusuma Junior High School in Bandung City use various expository learning strategies that are diverse and in accordance with the needs of students. Some of the commonly used expository learning strategies are lectures, demonstrations, directed discussions, interactive lectures, individual assignments, formative evaluations, and final summaries. Teachers use lectures to deliver a direct explanation of the material, while demonstrations are used to clarify certain concepts or processes. Focused discussions are used to facilitate interaction between students and teachers, while interactive lectures encourage active student participation. Individual assignments are used to actively engage students in the understanding and application of the material, while formative evaluations assist teachers in checking students' understanding. Final summaries are used to clarify students' understanding and allow time for final questions. This research makes an important contribution to the understanding of the application of expository learning strategies in PAI learning at Vijaya Kusuma Junior High School in Bandung City. The results of this study can be a reference for PAI teachers to develop more innovative and effective learning approaches. It is recommended to conduct further research with a larger sample and involving various schools in different cities or regions in order to get a more comprehensive picture of expository learning strategies in PAI lessons.Keyword: Learning Strategy; Expository Strategy; Islamic Education Lessons.